STUDENTS’ PERCEPTION ON THE USE OF ACTIVE LEARNING IN ENGLISH CLASS AT SMAN 1 SINGINGI - Anggi Milenia Sarahita; Erni Erni; M. Syarfi M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Teacher creativity in providing learning in the classroom is something that plays an important role in improving student learning abilities. Active Learning is a teaching method used by teachers in the classroom to improve students' learning abilities, both in increasing learning motivation, self-confidence, critical thinking and so on. In Active Learning there are various teaching techniques that can be used by teachers in teaching. The purpose of this study is to describe how students perceive the use of Active Learning in English classes at SMAN 1 Singingi. Cluster random sampling was used in determining two classes to represent the sample in this study. The sample in this study consisted of 43 students. The instrument used to collect data in this study was a questionnaire consisting of 20 statements. Data is scored using a Likert scale with four choices; Strongly Agree (SS), Agree (S), Disagree (TS), and Strongly Disagree (STS). The results showed that students' perceptions of Active Learning were high with an average score of 3.94. Therefore, it can be concluded that students have positive perceptions when learning in English class using Active Learning.Key Words : Perception, Students’ Perception, Active Learning